The Constitutional Court's Authority to Adjudicate Disputes Over Regional Head Election Results (Pilkada) Following MK Decision No. 85/PUU-XX/2022: A Siyasah Qadhaiyyah Perspective - Annisa D Putri Ramansyah; Bobang Noorisnan Pelita; Taufiq Alamsyah (al-Afkar, Journal For Islamic Studies, 2026)
Regional head election disputes require a constitutionally stable resolution mechanism. This study aims to analyze the shift in the Constitutional Court's authority following Decision Number 85/PUU-XX/2022 and its implications for legal certainty and separation of powers through a Siyasah Qadhaiyyah perspective. A normative juridical method was applied through analysis of legislation, court decisions, and Islamic constitutional law literature. The study finds that the decision permanently establishes the Court's authority over Pilkada disputes, yet produces jurisprudential inconsistency by reinterpreting constitutional norms without formal amendment, risking legal uncertainty and judicial overreach. In conclusion, from a Siyasah Qadhaiyyah perspective, this expansion deviates from the principles of justice, trustworthiness, and balance of power, necessitating a more consistent and accountable regulatory framework.